Combining Manure and Liquid Organic Fertilizer (LOF) and Its Effects on Livestock-Integrated Maize Farming Production (Zea Mays L) - Sumitro Hatibie; Kaimuddin; syamsuddin Garantjang (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2022)
This study aims to analyze the reaction in the doses of cow manure and liquid organic fertilizer and their reaction to the increase of farmer's revenue in a livestock-integrated farming system in Gorontalo. This study was performed in Gorontalo from March to July 2021. The study employed a 2-factor factorial design based on the randomized block design (RBD). The first factor is the cow manure dose and the second factor is the liquid organic fertilizer dose. Data were analyzed using ANOVA and the Tukey Honest Significant Difference (HSD) test. The results of the study concluded that the most optimal cow manure dose was 10 tons ha-1 to produce maize at a rate of 5.70 tons ha-1. 20 cc/14 L liquid organic fertilizer was able to generate the most optimal production of 5,67 tons ha-1. Integrating 10 tons ha-1 cow manure with 20 cc/14 L liquid organic fertilizer can generate the most optimal production amounting to 6.83 tons ha-1.